Analisis Pesan Simbolik Pada Ritual Adat Perkawinan Etnis Wangi-Wangi Kabupaten Wakatobi - Ashar Hasyim (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The problem in this study is how the process of the Wangi-Wangi Ethnic Marriage Ritual in Wakatobi Regency and how the meaning of symbolic messages in the traditional process of Wangi-Wangi ethnic marriage is in Wakatobi Regency. The research objectives are to analyze the process of the Wangi-Wangi Ethnic Marriage Ritual in Wakatobi Regency and to analyze the meaning of symbolic messages in the traditional process of Wangi-Wangi ethnic marriage in Wakatobi Regency. This research was conducted in the Wangi-Wangi Islands, Wakatobi Regency, Roland Bartens' semiotic theory (1957 in de Saussure), With 9 informants, the research method was using qualitative methods. The results showed that the Wangi-Wangi Ethnic Marriage Traditional Ritual has a very long series of traditional ceremonies and each Traditional Ritual has very good meanings for the bride and groom when they are married, which in this study the ritual processes are divided into 9 rituals.